2016
DOI: 10.1016/bs.pmbts.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

S-Glutathionylation and Redox Protein Signaling in Drug Addiction

Abstract: Drug addiction is a chronic relapsing disorder that comes at a high cost to individuals and society. Therefore understanding the mechanisms by which drugs exert their effects is of prime importance. Drugs of abuse increase the production of reactive oxygen and nitrogen species resulting in oxidative stress. This change in redox homeostasis increases the conjugation of glutathione to protein cysteine residues; a process called S-glutathionylation. Although traditionally regarded as a protective mechanism agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 193 publications
0
17
0
Order By: Relevance
“…In the nuclei, intensive declines in the content of free glutathione, GSH, and GSSG as well the GSH/GSSG ratio were observed; this can be explained by the increased protein conjugated glutathione levels (Figure 2). The protein S-glutathionylation induced by changes in the GSH/GSSG ratio provides a thiol redox-sensitive signaling mechanism in the cell (Ballatori et al, 2009; Hill and Bhatnagar, 2012; Womersley and Uys, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the nuclei, intensive declines in the content of free glutathione, GSH, and GSSG as well the GSH/GSSG ratio were observed; this can be explained by the increased protein conjugated glutathione levels (Figure 2). The protein S-glutathionylation induced by changes in the GSH/GSSG ratio provides a thiol redox-sensitive signaling mechanism in the cell (Ballatori et al, 2009; Hill and Bhatnagar, 2012; Womersley and Uys, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that plant MIR156 transcription is under epigenetic regulation, such as H2A.Z deposition, H3K4, or H3K27 methylation (Xu M. et al, 2016; Xu Y. et al, 2016; Hyun et al, 2017; Xu et al, 2018). Oxidative stress inhibits histone demethylation and increases protein S-glutathionylation via changes in the GSH/GSSG ratio rather than in the intracellular H 2 O 2 level (Hill and Bhatnagar, 2012; Niu et al, 2015; Womersley and Uys, 2016). GSH and the GSH/GSSG ratio therefore come to the forefront as redox regulation of vegetative phase change in higher plants.…”
Section: Discussionmentioning
confidence: 99%
“…ROS formation can lead to protein S-glutathionylation. This post-translational modification involves the covalent conjugation of the thiol group of reduced glutathione (GSH) to cysteine residues on proteins, which then can alter protein function (for review see (Womersley and Uys, 2016)). As METH increases ROS formation, METH may affect VMAT2 function and DA vesicular packaging through this protein modification (Uys et al, 2014).…”
Section: Ros Impair Vmat2 Functionmentioning
confidence: 99%
“…Immediate early gene, which alters gene expression in response to external stimuli (Hope et al, 1992;Nestler et al, 1993) Increased by cocaine administration (Hope et al, 1992) Cofilin (Fratelli et al, 2002) Human T lymphocytes Depolymerizes filamentous actin into globular actin (Calabrese et al, 2014) Actin cycling is required for drug-induced neuroplasticity ( Cyclin-dependent kinase 5 is a multifunctional serine/threonine kinase implicated in cytoskeletal reorganization, Cytoskeletal reorganization plays a key role in synaptic plasticity, which is integral to drugrelated learning and memory (Luscher, 2013) Cytochrome c oxidase (Fratelli et al, 2002) Human Human erythrocytes Primarily involved in energy metabolism but also forms a complex with glutamatergic AMPA receptors May play a role in glutamatergic signaling and is involved in the stimulant effects of cocaine when nitrosylated Xu et al, 2013) GSTP (Townsend et al, 2009) HEK293 cells Phase II detoxification enzyme that catalyzes the conjugation of glutathione to low pK a protein thiols, i.e., S-glutathionylation (Dalle-Donne et al, 2007) Drug-induced oxidative stress increases Sglutathionylation, which may induce structural and functional changes in proteins involved in the response to drugs of abuse (Womersley & Uys, 2016). GSTP activity has been implicated in the psychomotor effects of cocaine Heat shock protein 60 (Fratelli et al, 2002) Human T lymphocytes Mitochondrial chaperonin involved in protein folding and transport (Zill et al, 2011) HSP60 was reduced in the amygdala of opiate addicts (Zill et al, 2011) Heat shock protein 70 (Mullen et al, 2015) Human monocytic cells Molecular chaperone and protein folding (Mayer & Bukau, 2005) HSP70 in the nucleus accumbens has been implicated in the development of behavioral sensitization to morphine (Qin et al, 2013;Wang et al, 2014b) Histone H3 (Garcia-Gimenez et al, 2013) NIH3T3 cells A core subunit of the nucleosome, which is responsible for maintaining chromatin structure (Filipescu et al, 2014) Histone H3 acetylation in the nucleus accumbens shell is associated with cocaine self-administration (Wang et al, 2010) and locomotor activity (Kumar et al, 2005)…”
Section: Potential Therapies For Addiction May Influence Redox Statusmentioning
confidence: 99%
“…However, a detailed list of all proteins which undergo S‐glutathionylation, as well as the functional impact of this modification on addiction, is not currently possible as the role of redox signaling and more specifically S‐glutathionylation is still a relatively new topic of investigation. A previous review identified several proteins that undergo S‐glutathionylation and are suggested to play a role in the response to drugs of abuse (Womersley & Uys, ). Included in this list were proteins involved in diverse functions such as cytoskeletal structure, cellular signaling and dopamine metabolism, indicating that S‐glutathionylation may act on multiple different processes that underlie the response to drugs of abuse.…”
Section: S‐glutathionylation Of Proteins Integral To the Response To mentioning
confidence: 99%